Electron-structure calculations and bond order analysis using density functional theory of cationic dinuclear arene ruthenium complexes - Penka Fowe, Emmanuel; Therrien, Bruno; Süss-Fink, Georg; Daul, Claude (My University, 2008)
The structure and nature of the metal-metal bonding interaction in the cationic complexes [(?6-C6Me6)2Ru2(?-H)n(?-1,4-SC6H4Br-?S:?S)3-n] (1-4; n = 0-3) were studied at the d. functional theory (DFT) level using MO theory, bond order (BO) anal., bond decompn. energy (BDE), electron localization function (ELF), and Laplacian of the d. methods. The results show that there is no direct bond between the two ruthenium atoms in 1-4, the MO interaction within the diruthenium backbone being stabilized by the bridging ligands. For complex 1, the ELF clearly shows that the bond within the diruthenium backbone is through the three bridging hydride ligands, which act as a sort of glue by forming three-center two-electron bonds characterized by (Ru, H, Ru) basins with 1.8 e mostly located in the H at. basin. [on SciFinder(R)]
Keywords: ruthenium arene binuclear hydride benzenethiolate optimized structure bond order; bond order metal metal ruthenium arene binuclear hydride benzenethiolate; hydride benzenethiolate bridged diruthenium arene complex bond order calcn